Determinants of rice by-products utilization as feed and their management in Ethiopia: the case of Fogera District - ASMARE, BIMREW; YAYEH, ZEMENU (Asian Journal of Agriculture, 2018)
Asmare B, Yayeh Z. 2018. Determinants of rice by-products utilization as feed and their management in Ethiopia: the case of Fogera District. Asian J Agric 2: 1-7. The study was conducted with the objective to determine the status of farmers’ rice byproduct utilization as feed in Fogera district, northwestern Ethiopia. Eighty smallholder farmers were selected purposely based on livestock population and rice production access. A semi-structured questionnaire was administered to select farmers systematically. The collected data was analyzed using SPSS descriptive statistical analysis. The result indicated that the majority of respondents in the study area were with the range from 31 to 50 years (55%). Education status of respondents showed that the majority of household heads were able to read and write (27.5%) followed by elementary school (26.25%) and high school (17.5%) completed. The main dry season feed in the majority of households (46.25%) was found to be grazing and crop residues. The majority (64.62%) of farmers used rice by-products as livestock feed, followed by both feed and house construction. Types of by-products used for animal feed by respondent’s elucidated majority (61.5%) used rice straw, considerable proportion (26.15%) rice bran and (12.30%) used both straw and bran for animal feed based on availability. The sources of rice by-products indicated for many of respondents (66.7%) was farm produced, 18.5% use purchased and 18.4% get rice by-products both from farm produced and purchasing for their animal feed. Type of animals fed rice byproducts including cattle in the case of majority of respondents (49.23%), cattle and equine, followed (24.62%), and all animals (13.85%), respectively. In livestock owners, rice by-products are fed to livestock as sole feed and mixed with other feeds, however, the majority (69.2%) of households provides sole followed by both sole and mixed with other feeds (16.9%). Many of the respondents (55%) apply drying followed by addition of salt water (22.5%) as method of improving the rice by-products. The main constraints observed in rice by-products utilization as feed were seasonal deficiency of by-products (25.5%) followed by lack of awareness (16.25%).Though these problems prevailed in the study area, rice by-products are being used as a major crop residue feed with little or no improvement applied. Generally, it can be included that rice by-products were found very important feed resources in the rice dominated farming system of Fogera district. To exploit these products properly, farmers need to be assisted through proper agricultural extension service and supply in the form of credit service. Moreover, further on detailed on-farm experimentation should be done to demonstrate better utilization of the products as livestock feed.